2022
DOI: 10.32604/csse.2022.018430
|View full text |Cite
|
Sign up to set email alerts
|

A Particle Swarm Optimization Based Deep Learning Model for Vehicle Classification

Abstract: Image classification is a core field in the research area of image processing and computer vision in which vehicle classification is a critical domain. The purpose of vehicle categorization is to formulate a compact system to assist in real-world problems and applications such as security, traffic analysis, and selfdriving and autonomous vehicles. The recent revolution in the field of machine learning and artificial intelligence has provided an immense amount of support for image processing related problems an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The swarm behavior of organisms is the basis of mimic that followed by swarm intelligence (SI) techniques, which lives and cooperates with each other in groups. Alhudhaif Adi et al used the PSO is also in deep learning for feature optimization and reduction using nature-based PSO [20]. As examples of the SI algorithms are PSO [21], ACO [22], Dragonfly Algorithm (DA) [23], Salp Swarm Algorithm (SSA) [24], Grey Wolf Optimizer (GWO) [25], FA [26], and SFLA [27].…”
Section: Introductionmentioning
confidence: 99%
“…The swarm behavior of organisms is the basis of mimic that followed by swarm intelligence (SI) techniques, which lives and cooperates with each other in groups. Alhudhaif Adi et al used the PSO is also in deep learning for feature optimization and reduction using nature-based PSO [20]. As examples of the SI algorithms are PSO [21], ACO [22], Dragonfly Algorithm (DA) [23], Salp Swarm Algorithm (SSA) [24], Grey Wolf Optimizer (GWO) [25], FA [26], and SFLA [27].…”
Section: Introductionmentioning
confidence: 99%
“…Most MAs are inspired by human intelligence, the social nature of biological groups, and the laws of natural phenomena. Some classic representatives of MAs, such as genetic algorithm (GA) [10], particle swarm optimization (PSO) [11], differential evolution (DE) [12], grey wolf optimizer (GWO) [13], Harris hawks optimizer (HHO) [14], bat algorithm (BA) [15], whale optimization algorithm (WOA) [16], salp swarm algorithm (SSA) [17], sine cosine algorithm (SCA) [18], water cycle algorithm (WCA) [19], and so on, have been successfully used to solve some complex optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…The hyper-parameter selection in deep neural networks using Parallel PSO too was discussed by Lorenzo et al ( 2017b ). A PSO based deep learning model for vehicle classification (Alhudhaif, 2022 ), image classification (Junior and Yen, 2019 ), hyper spectral image classification (Liu X. et al, 2021 ), and flash flood detection from satellite images (Tuyen et al, 2021 ) too was reported in the literature. A text feature selection using the PSO algorithm was implemented by Zahran and Kanaan ( 2009 ).…”
Section: Introductionmentioning
confidence: 99%